Langghar dan Taman Pendidikan Qur’an: Studi Komparasi Tes Baca Al-Qur’an dengan Metode Konvensional - Mutammimah, Darun; Sa’diyah, Halimatus (Lembaga Yasin AlSys, 2025)
The declining interest of communities in langghar as traditional educational institutions has coincided with growing preference for TPQ, which are perceived as more structured and effective in Al-Qur’an instruction, thereby necessitating a comparative study on the effectiveness and relevance of both within the context of community Al-Qur’an education. This study aimed to analyse differences in the effectiveness of Al-Qur’an reading instructional methods between langghar that employ conventional methods and TPQ that apply the Ummi method, as well as to compare the relevance and appeal of both institutions in the community’s socio-religious context. A mixed-methods approach with an explanatory sequential design was employed at Langghar Baitul Amal, Langghar Darun Najah, and TPQ Sahabat Qur’an, involving santri in grades 4–6 of elementary school. Quantitative data were obtained through Al-Qur’an reading ability tests and analysed using descriptive statistics (means) and the Mann–Whitney U test, while qualitative data were collected through interviews, observations, and documentation, and subsequently analysed thematically. The results showed significant differences in tartil and fashohah abilities between TPQ and langghar santri (p < 0.05), with TPQ santri achieving higher outcomes, whereas langghar continued to demonstrate strong relevance in shaping spiritual character and preserving the religious traditions of Madurese society. These findings affirm that TPQ are pedagogically more effective due to their structured instructional system, while langghar are effective in the internalisation of religious values through close emotional bonds between teachers and santri, such that both institutions complement one another within the contemporary Al-Qur’an education ecosystem. This study is expected to enrich the body of knowledge and raise public awareness of the importance of Al-Qur’an education and socio-religious life.